2022
DOI: 10.1002/advs.202204683
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Single Pulse Switching of [Co/Gd/Pt]N Nanodisks Using Surface Lattice Resonances

Abstract: The impact of plasmonic surface lattice resonances on the magneto-optical properties and energy absorption efficiency has been studied in arrays of [Co/Gd/Pt] N multilayer nanodisks. Varying the light wavelength, the disk diameter, and the period of the array, it is demonstrated that surface lattice resonances allow all-optical single pulse switching of [Co/Gd/Pt] N nanodisk arrays with an energy 400% smaller than the energy needed to switch a continuous [Co/Gd/Pt] N film. Moreover, the magneto-optical Faraday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Additionally, the induced electron temperature has a Gaussian-like intensity distribution, which is similar to the localized electromagnetic field distribution. Recently, it has been shown that surface lattice resonance can be utilized to control the distribution of electric fields and thereby regulate the efficacy of ultrafast demagnetization and all-optical switching. ,, Although we focus on localized surface plasmon resonance in the present work, our multiphysics model can be readily applied to investigate the influence of surface lattice resonance on ultrafast magnetism at the nanoscale.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Additionally, the induced electron temperature has a Gaussian-like intensity distribution, which is similar to the localized electromagnetic field distribution. Recently, it has been shown that surface lattice resonance can be utilized to control the distribution of electric fields and thereby regulate the efficacy of ultrafast demagnetization and all-optical switching. ,, Although we focus on localized surface plasmon resonance in the present work, our multiphysics model can be readily applied to investigate the influence of surface lattice resonance on ultrafast magnetism at the nanoscale.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Recently Pezeshki et al [158] proposed an integrated hybrid plasmonic-photonic device that is based on AOS. Verges et al [159] showed that using [Co/Gd/Pt] N nanodisks, instead of their films, reduces the energy to have a single pulse switching by 400%. We are hopeful that new and often surprising breakthroughs are possible in the next decade.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kiriliyuk and co-workers observed thermal demagnetization dynamics in TbCo alloy driven by plasmonic excitations in nanoscale Ag rings 88 , and a similar approach was also reported by Stupakiewicz and colleagues in Au/YIG:Co magneto-plasmonic crystals 89,90 . Finally, in two recent independent works, it has been shown that plasmon-enhanced phenomena can drive more efficient magnetization dynamics and switching 91,92 . Again, all these pioneering studies are limited by the duration of the light pulses used to either excite or probe the magnetization dynamics, thus hindering the possibility to access sub-100 fs magnetic processes in magnetoplasmonic nanomaterials in pump-probe experiments.…”
Section: Introductionmentioning
confidence: 93%